2014
DOI: 10.1111/maec.12157
|View full text |Cite
|
Sign up to set email alerts
|

High environmental salinity reduces the reproductive potential of the spider crab Maja brachydactyla (Decapoda, Majidae)

Abstract: The spider crab Maja brachydactyla is an important fisheries species in Europe. Adults were sampled in R ıa de A Coruña (NW Spain) and transported to IRTA rearing facilities. Salinity and photoperiod changes and their effect on reproduction were tested in the laboratory. The number of newly hatched larvae per batch (presence of actively swimming newly hatched larvae in a broodstock tank) was counted and sampled to estimate dry weight and proximal composition. Keeping spider crab broodstock in a high salinity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…The MAC region is not influenced by estuaries and has high and constant salinity levels when compared to the other studied regions. According to Rotllant, Simeó, Maciá, and Estévez (2014) in studies with Majabrachy dactyla Balss, 1922, higher salinities decrease larval survival, which is a limiting factor to the life cycle of the species. The intolerance to variations in salinity was also observed for the congeneric species Libinia emarginata Leach, 1815 (Charmantier, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAC region is not influenced by estuaries and has high and constant salinity levels when compared to the other studied regions. According to Rotllant, Simeó, Maciá, and Estévez (2014) in studies with Majabrachy dactyla Balss, 1922, higher salinities decrease larval survival, which is a limiting factor to the life cycle of the species. The intolerance to variations in salinity was also observed for the congeneric species Libinia emarginata Leach, 1815 (Charmantier, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The MAC region is not influenced by estuaries and has high and constant salinity levels when compared to the other studied regions. According to Rotllant, Simeó, Maciá, and Estévez (2014) in studies with Majabrachy dactyla Balss, F I G U R E 5 Libinia ferreirae (a) and L. spinosa (b), image found in association with jellyfish. Abundance of free-living crabs and associated with the jellyfish L. lucerna temporarily distributed in the study regions (MAC, UBA and SFS)…”
Section: Crabs In Associationmentioning
confidence: 99%
“…The distribution pattern observed in this study allows us to infer that adult crabs are most likely to be found in areas with higher salinity and temperatures, so the variation in salinity likely drives the abundance of ovigerous females (the number of ovigerous females tended to increase as salinity increased). Studying Maja brachydactyla Balss, 1922, Rotllant et al (2014 concluded that salinities higher than 38 ppt can drastically decrease larval survival and be a limiting factor in the life cycle of this species. Such intolerance to salinity was also observed in a congener species by Charmantier (1998), who showed that many Majoidea crabs, such as L. emarginata and Chionoecetes opilio (O. Fabricius, 1788), are weak regulators (or osmoconformers), which is an important factor in the settlement of many crustacean species.…”
Section: The Influence Of Environmental Factorsmentioning
confidence: 99%
“…The production of a large number of specimens, for both commercial and stock enhancement purposes, requires a lot of prior knowledge. A considerable number of studies on the production, i.e., the reproduction and growth under captivity conditions, of Maja brachydactyla have been conducted in the last few years (e.g., Castejón et al, 2015;Domingues et al, 2012;Guerao et al, 2012;Rotllant et al, 2015;Simeó et al, 2015).However, information about M. squinado is scarce. Just a few studies on the reproductive process, larval rearing and growth under intensive culture conditions have been published (Durán et al, 2012;Durán et al, 2013;Guerao et al, 2008;Guerao and Rotllant, 2010).…”
Section: Introductionmentioning
confidence: 99%